Efek Ekstrak Daun Kelor (Moringa Oleifera) Dalam Menghambat Aktifasi NFkB, Ekspresi TNF-adan ICAM-1 pada HUVECS yang Dipapar LDL Teroksidasi - Titin Andri Wihastuti; Djanggan Sargowo; M Saifur Rohman (The Indonesian Heart Association, 2007)
Background. Atherosclerosis is a chronic inflammation process of vascu-lar endothelial cells. Increased oxydized LDL(OxLDL) is one of the most potent inducer of atherogenesis. OxLDL induces an increased ROS (Reac-tive Oxigen Species) and also acts as cytotoxic and chemotaxis factor for monocytes result in accumulation of inflammatory cells. Nuclear Factor Kappa Beta(NFkB) is a transcription factor that plays an important role in this inflammatory proces. NFkB compose of heterodimer molecules of p50 and p65, which bind to its inhibitor, IkB, leading to its inactive form in cytoplasm. OxLDL activates NFkB complex by phosphorylate IkB resulting in released p50-p65-IkB binding and translocation of p50-p65 into the nucleus. p50-p65 then binds to promoter and activates transcription of target genes. NFkB activation therefore increase gene and protein expressions of target molecules such TNF-a, ICAM-1, VICAM, etc. This study aimed to examine whether Moringa oleiferainhibits activation of NFkB dan expression of cytokine TNF-aand adhesion molecule ICAM-1.Methods and results.Human umbilical vein endothelial cells (HUVECs) treated with OxLDL were used as model of atherosclerosis. The increased NFkB activity was measured by indirect method using p50 subcellular lo-calization by immunohistochemistry. 40ug/mL OxLDL, 0.01 gr/mL and 0.005 gr/mL Moringa oleiferawere used based on preliminary study.Conclusions. This study showed that OxLDL significantly induce NFkB activation and increase protein expression of TNF-aand (ICAM-1). This study also observed that Moringa oleiferasignificantly inhibit NFkB activa-tion, and prevent an increased TNF-aand ICAM-1 expression at protein level in OxLDL-treated HUVECs as compare to the controls. Moringa oleifera dose of 0.01mg/mL has a better inhibition effect as compare to that of 0.005 gr/mL.